A low-temperature curing conductive adhesive for perovskite-silicon heterojunction tandem solar cells

By developing a low-temperature curing conductive adhesive containing a composite curing agent containing boron trifluoride complex and tertiary amine compound, the existing conductive adhesive has solved the problems of high curing temperature, short application period, poor fine line printing and poor electrical performance, and has achieved rapid low-temperature curing, good printing and high electrical performance, which is suitable for the preparation of perovskite-silicon heterojunction stacked solar cells.

CN116355569BActive Publication Date: 2025-03-11WENZHOU LONGSUN ELECTRICAL ALLOY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310379069.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-11
Publication Date
2025-03-11
Estimated Expiration
2043-04-11

AI Technical Summary

Technical Problem

When preparing perovskite-silicon heterojunction stacked solar cells, the existing conductive glue has high curing temperature, short application period, poor fine line printing, and poor electrical performance, which cannot meet the requirements of high conversion efficiency and low cost.

Method used

A low-temperature curing conductive adhesive was developed, containing 85-95 wt.% conductive powder, 1-10 wt.% flexible thermosetting compound, 1-10 wt.% epoxy resin, 0.1-10 wt.% compound curing agent, 1-5 wt.% diluent and 0.1-1 wt.% additive. Boron trifluoride complexes and tertiary amine compounds were used as compound curing agents to reduce the activation energy of the curing reaction and achieve rapid curing at low temperature.

Benefits of technology

The conductive glue curing temperature is less than 150°C and the curing time is less than 15 minutes. It has good fine line printing and electrical properties, long application period and low cost, and is suitable for the preparation of perovskite-silicon heterojunction stacked solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005231127850000111
    Figure GDA0005231127850000111
Patent Text Reader

Abstract

The present invention discloses a low-temperature curing conductive adhesive for perovskite-silicon heterojunction stacked solar cells, which comprises, by weight percentage: 85-95wt.% conductive powder, 1-10wt.% flexible thermosetting compound, 1-10wt.% epoxy resin, 0.1-10wt.% compound curing agent, 1-5wt.% diluent, 0.1-1wt.% auxiliary agent. The compound curing agent comprises two or more of boron trifluoride complex, acetylacetone metal salt, organic titanate, borofluoride metal salt, phenol, organic sulfonic acid, boric acid, and tertiary amine compound; the compound curing agent also comprises one or two of benzyl alcohol and polyethylene glycol. The curing temperature of the conductive adhesive is less than 150°C, the curing time is less than 15min, the printing screen opening is less than 30μm, the fine line printing performance is excellent, the photoelectric conversion efficiency is high, the application period is long, the cost is low, and batch industrial production can be carried out.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cells, and in particular relates to a conductive adhesive used for solar cells. Background Art

[0002] The energy distribution of the solar spectrum is relatively wide, and any semiconductor material can only absorb photons with energy values ​​greater than its bandgap width. Therefore, a wide bandgap material can be stacked on the top of a silicon cell to form a stacked cell, broadening the spectral response of the cell, maximizing the use of solar energy, and improving the efficiency of solar cells. Since perovskite and silicon have different band gaps, perovskite solar cells can be used as top cells to form stacked solar cells with silicon cells, namely perovskite-silicon heterojunction stacked solar cells. The perovskite top cell uses a transparent indium tin oxide (ITO) or indium zinc oxide (IZO) film instead of Au as a conductive layer, and then prints a conductive glue on the transparent oxide conductive layer to prepare an Ag grid electrode for collecting carriers transmitted to the conductive layer. This stacked solar cell broadens the spectral response range of the cell, improves the efficiency of the solar cell, and reduces the preparation cost.

[0003] Since the thermal stability of organic-inorganic perovskite (ABX3) materials will be destroyed when the temperature exceeds 150°C, and high temperature will also damage the performance of the hole transport layer material (spiro-OMeTAD), reducing the conversion efficiency of the stacked solar cells; and the low-temperature silver paste used in high-efficiency heterojunction (HJT) solar cells has a curing temperature of more than 180°C, which is no longer suitable for the high conversion efficiency and low cost requirements of perovskite-silicon heterojunction stacked solar cells. At present, conductive adhesives with a curing temperature below 150°C mainly include two-component conductive adhesives, single-component conductive adhesives and thermoplastic conductive adhesives. However, there are still many technical problems with the above conductive adhesives. For example, two-component conductive adhesives are inconvenient to use at the production line end, and the applicable period is extremely short (less than 4h); single-component conductive adhesives have a short applicable period (less than 30 days), a long curing time (150°C curing time is greater than 30min, usually 60min), and a high resistivity; thermoplastic conductive adhesives cannot meet the requirements of fine line printing and electrical performance due to their poor printability. Therefore, there is an urgent need to develop a single-component conductive adhesive suitable for perovskite-silicon heterojunction stacked solar cells. The curing temperature of the single-component conductive adhesive should be lower than 150°C, and at the same time meet various requirements such as good fine line printing, good electrical properties, long applicability, short curing time, and low cost. Summary of the invention

[0004] In view of the problem that low-temperature silver paste in the prior art cannot meet the needs of perovskite-silicon heterojunction stacked solar cells, the purpose of the present invention is to provide a low-temperature curing conductive adhesive for perovskite-silicon heterojunction stacked solar cells, wherein the low-temperature curing conductive adhesive has a curing temperature of less than 150°C, a curing time of less than 15 minutes, a printing screen opening of less than 30 μm, good fine line printability, high photoelectric conversion efficiency, long application period, short curing time and low cost.

[0005] The present invention provides a low-temperature curing conductive adhesive for perovskite-silicon heterojunction stacked solar cells, which comprises, by mass percentage, 85-95wt.% conductive powder, 1-10wt.% flexible thermosetting compound, 1-10wt.% epoxy resin, 0.1-10wt.% compound curing agent, 1-5wt.% diluent, and 0.1-1wt.% auxiliary agent.

[0006] Preferably, the low-temperature curing conductive adhesive for perovskite-silicon heterojunction stacked solar cells comprises, by mass percentage: 87-92wt.% conductive powder, 2-4wt.% flexible thermosetting compound, 1.5-3wt.% epoxy resin, 0.6-2wt.% compound curing agent, 1.5-5wt.% diluent, and 0.5-1wt.% auxiliary agent.

[0007] Specifically, the composite curing agent includes component A and component B; component A includes two or more of boron trifluoride complexes, acetylacetone metal salts, organic titanates, borofluoride metal salts, phenols, organic sulfonic acids, boric acid, and tertiary amine compounds; and component B includes one or two of benzyl alcohol and polyethylene glycol.

[0008] The compound curing agent is prepared by the following method: adding component A to component B, heating, dissolving, and fully stirring to obtain a liquid compound curing agent. Compared with the prior art, the compound curing agent provided by the present invention can greatly reduce the activation energy of the epoxy curing reaction of the conductive adhesive, reduce the curing reaction temperature, and make the epoxy resin system in the conductive adhesive quickly cure below 150°C, and make the conductive adhesive have a longer application period while maintaining good cured product performance.

[0009] Furthermore, in the composite curing agent, component A at least includes a boron trifluoride complex and a tertiary amine compound, and the boron trifluoride complex and the tertiary amine compound need to be used in combination. In parts by mass, the ratio of the boron trifluoride complex to the tertiary amine compound is (3 to 8): 1. In the boron trifluoride complex, taking boron trifluoride triethanolamine as an example, the boron atom in boron fluoride has an empty orbital and can accept the lone pair of electrons of the nitrogen atom in triethanolamine. Boron fluoride acts as a Lewis acid and the triethanolamine compound acts as a Lewis base, and the two form a Lewis complex. In the composite curing agent described in the present invention, the combination of the boron trifluoride complex and the added tertiary amine compound makes the stability of the complex more excellent, which helps to extend the application period of the conductive adhesive. Similarly, acetylacetone metal salts, organic titanates, borofluoride metal salts, phenols, organic sulfonic acids, and boric acid in the composite curing agent can also be used as Lewis acids to form Lewis acid complexes in combination with tertiary amines. Taking boron trifluoride-amine complex as an example, during the curing stage of the conductive adhesive containing the complex, the boron trifluoride-amine complex is rapidly decomposed into BF3 and amine when heated (<150°C), and the amine and the epoxy resin in the conductive adhesive undergo a curing reaction. At the same time, BF3 has the effect of promoting the curing reaction of the epoxy group and the amine. In addition, the stable boron trifluoride-amine complex makes the corresponding conductive adhesive have a longer application period at room temperature.

[0010] Preferably, in component A of the composite curing agent, the ratio of boron trifluoride complex, borofluoride metal salt, organic sulfonic acid and tertiary amine compound is (3-8): (3-5): (1-3): 1 in parts by mass.

[0011] Preferably, in component A of the composite curing agent, the ratio of boron trifluoride complex, acetylacetone metal salt and tertiary amine compound is (3-8): (1-2): 1 in parts by mass.

[0012] Furthermore, component B of the composite curing agent includes benzyl alcohol and polyethylene glycol. In parts by mass, the ratio of component A, benzyl alcohol and polyethylene glycol of the composite curing agent is (1.5-5):(1-2.5):1.

[0013] Specifically, the boron trifluoride complex is selected from one or more of boron trifluoride ethyl ether, boron trifluoride phenol, boron trifluoride piperidine, boron trifluoride acetate, boron trifluoride monomethylamine, boron trifluoride monoethylamine, boron trifluoride triethanolamine, boron trifluoride monoethanolamine, boron trifluoride-2,4-dimethylaniline, boron trifluoride triethanolamine, and boron trifluoride benzylamine, preferably one or more of boron trifluoride-2,4-dimethylaniline, boron trifluoride triethanolamine, and boron trifluoride benzylamine.

[0014] Specifically, the metal salt of acetylacetonate is selected from one or more of aluminum acetylacetonate, zinc acetylacetonate, indium acetylacetonate, copper acetylacetonate, and nickel acetylacetonate.

[0015] Specifically, the phenols are selected from one or more of phenolic acid, resorcinol and cresol.

[0016] Specifically, the organic sulfonic acid is selected from one or more of benzenesulfonic acid, toluenesulfonic acid, cycloalkanesulfonic acid, and p-toluenesulfonic acid.

[0017] Specifically, the tertiary amine compound is selected from one or more of 2methyl-2-hydroxydecylamine, triethanolamine, 2ethyl-2-hydroxyhexadecylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and melamine, preferably 2methyl-2-hydroxydecylamine or triethanolamine.

[0018] Specifically, the conductive powder is one or more of silver powder, silver-coated copper powder, silver-coated nickel powder, copper powder, and copper-tin-silver alloy powder. The use of a variety of base metal conductive powders reduces the production cost of the conductive adhesive without affecting the photoelectric conversion efficiency of the solar cell.

[0019] Furthermore, the conductive powder morphology is spherical powder and flaky powder, and the mass ratio of spherical powder to flaky powder is preferably (99:1) to (1:99); wherein the spherical powder particle size distribution is D90≤6μm, D50≤4μm, tap density is 3-8g / ml, and specific surface area is 0.2-2.5m 2 / g; the flake powder has a flake size distribution of D90≤15μm, D50≤8μm, a tap density of 3-8g / ml, and a specific surface area of ​​0.3-1.5m 2 / g.

[0020] Based on the conductive powder, it is preferred that the mass ratio of the spherical conductive powder to the flake conductive powder is 1:(0.5-2).

[0021] Specifically, the flexible thermosetting compound has an average functionality of 2 to 7 and a number average molecular weight of 500 to 8,000.

[0022] Further, the flexible thermosetting compound includes a prepolymer of a compound containing an isocyanate group and a polyester polyol, a prepolymer of a compound containing an isocyanate group and a polyether polyol, or a prepolymer of a compound containing an isocyanate group and a polycarbonate polyol; the compound containing an isocyanate group and the prepolymer containing an isocyanate group have been end-capped with a pyrazole, oxime, or imidazole compound; or

[0023] The flexible thermosetting compound is selected from a mixture of two or more of terminal hydroxyl polybutadiene, epoxidized polybutadiene, saturated polyester resin, unsaturated polyester resin, epoxy resin and isocyanate compounds; the isocyanate compound is preferably blocked isocyanate (XDI).

[0024] Specifically, the epoxy resin has an average functionality of 2 to 7 and an epoxy equivalent of 100 to 900; the epoxy resin is selected from one or more of glycidyl ether epoxy resins, glycidyl ester epoxy resins, glycidyl amine epoxy resins, alicyclic epoxy resins and phenolic epoxy resins.

[0025] Preferably, the glycidyl ether epoxy resin is selected from one or more of bisphenol A type, bisphenol F type, hydrogenated bisphenol A type, aliphatic glycidyl ether resin and the like.

[0026] Specifically, the diluent includes at least one of an active diluent and an inactive diluent, with a solubility parameter of 6 to 12δ, a boiling point of 130 to 220° C., and a volatilization rate of less than 2.5.

[0027] Preferably, the reactive diluent is selected from one or more of 2-ethylhexyl glycidyl ether, ethylene glycol diglycidyl ether, hexanediol diglycidyl ether and the like.

[0028] Preferably, the inactive diluent is selected from one or more of ethylene glycol butyl ether, propylene glycol methyl ether acetate, ethylene glycol ethyl ether acetate, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, diethylene glycol ethyl ether acetate, and N-methylpyrrolidone.

[0029] Specifically, the auxiliary agent is one or more of oleic acid, sorbitan trioleate, sorbitan tristearate, ethylene glycol fatty acid ester, and castor oil polyoxyethylene ether.

[0030] The present invention also provides a method for preparing a low-temperature curing conductive adhesive for a perovskite-silicon heterojunction stacked solar cell, comprising the following steps:

[0031] Step 1: Mix the flexible thermosetting compound, epoxy resin, compound curing agent, diluent and additive according to the proportion, stir the materials in the container with a disperser to make them evenly mixed, and then add the conductive powder according to the proportion;

[0032] Step 2: Use a dispersing mixer to stir all the materials in the container to make them evenly mixed, and let them stand for several hours to allow the powder to be fully infiltrated to obtain a premixed mixture;

[0033] Step 3: Use a three-roll mill to further disperse and mix the mixture so that each component is evenly dispersed; wherein the gap between the discharge rollers of the three-roll mill is 8 to 15 um;

[0034] Step 4: The rolled mixture is filtered through a filter to remove large-sized agglomerates and conductive powder to obtain a low-temperature curing conductive adhesive for perovskite-silicon heterojunction stacked solar cells; the filter mesh number is preferably 400 to 600 meshes.

[0035] The low-temperature curing conductive adhesive for perovskite-silicon heterojunction stacked solar cells provided by the present invention can be used to prepare grid line electrodes for perovskite-silicon heterojunction stacked solar cells. The application method is generally: the low-temperature curing conductive adhesive is subjected to a screen printing process and / or a mesh-free screen to obtain a grid line electrode.

[0036] The present invention also provides a grid line electrode for a perovskite-silicon heterojunction stacked solar cell, which is prepared by using the low-temperature curing conductive adhesive for the perovskite-silicon heterojunction stacked solar cell through a screen printing process and / or a mesh-free screen.

[0037] By adopting the above technical solution, the low-temperature curing conductive adhesive for perovskite-silicon heterojunction stacked solar cells provided by the present invention has the following beneficial effects:

[0038] The present invention provides a low-temperature curing conductive adhesive for perovskite-silicon heterojunction stacked solar cells, which uses a composite curing agent mainly composed of a boron trifluoride complex and a tertiary amine compound. Taking the composite curing agent containing a boron trifluoride-amine complex as an example, the composite curing agent is in the curing stage of the conductive adhesive. The boron trifluoride-amine complex is rapidly decomposed into BF3 and amine when heated at low temperature (<150°C) for curing. The amine and the epoxy resin in the conductive adhesive react with each other, and at the same time, BF3 has the effect of promoting the curing reaction of the epoxy group and the amine. In addition, the combination of the boron trifluoride-amine complex and the tertiary amine compound makes the stability of the complex more excellent, and the corresponding conductive adhesive has a longer applicable period at room temperature, and can be stored at 5°C for more than 3 months. Compared with the prior art, the low-temperature curing conductive adhesive provided by the present invention uses base metals as conductive powders, which greatly reduces the manufacturing cost, so that the stacked solar cell has a higher photoelectric conversion efficiency and a longer applicable period, while further improving the production line production efficiency and reducing the production cost. DETAILED DESCRIPTION

[0039] The following describes the embodiments of the present invention through specific embodiments, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the following embodiments and features in the embodiments can be combined with each other without conflict.

[0040] The present invention provides a low-temperature curing conductive adhesive for perovskite-silicon heterojunction stacked solar cells, which comprises, by weight percentage: 85-95wt.% conductive powder, 1-10wt.% flexible thermosetting compound, 1-10wt.% epoxy resin, 0.1-10wt.% compound curing agent, 1-5wt.% diluent, and 0.1-1wt.% auxiliary agent.

[0041] Specifically, the compound curing agent is one or more of boron trifluoride complexes, acetylacetonate metal salts, organic titanates, borofluoride metal salts, phenols, organic sulfonic acids, boric acid, and tertiary amine compounds. Further, the compound curing agent is added with benzyl alcohol and polyethylene glycol in a certain proportion, and a liquid mixture is formed by dehydration, heating, and stirring.

[0042] As a preferred embodiment, the compound curing agent A is prepared by the following method:

[0043] 96g of 45% [BF4]2Ni aqueous solution and 44g of 400 # The polyethylene glycol mixture is heated, dried and dehydrated in a vacuum oven at 110° C. to form component 1; 90 g of component 1, 90 g of boron trifluoride-2,4-dimethylaniline, 60 g of benzyl alcohol, 24 g of p-toluenesulfonic acid, and 12 g of 2-methyl-2-hydroxydecylamine are weighed and mixed, and heated to dissolve at 55-60° C. to obtain a liquid composite curing agent A.

[0044] As a preferred embodiment, the compound curing agent B is prepared by the following method:

[0045] 90g of triethanolamine boron trifluoride, 15g of zinc acetylacetone, 25g of 400 # Polyethylene glycol, 60 g of benzyl alcohol and 15 g of 2-methyl-2-hydroxydecylamine were weighed and mixed, and heated to 85-90° C. to dissolve, thereby obtaining a liquid composite curing agent B.

[0046] As a preferred embodiment, the compound curing agent C is prepared by the following method:

[0047] 60g of benzylamine boron trifluoride, 60g of benzyl alcohol, 60g of 400 # Polyethylene glycol, 25 g of aluminum acetylacetone and 15 g of triethanolamine were weighed and mixed, and heated to 70-75° C. to dissolve to obtain a liquid composite curing agent C.

[0048] The present invention is further described below in conjunction with specific embodiments.

[0049] Embodiment 1:

[0050] A low-temperature curing conductive adhesive for perovskite-silicon heterojunction stacked solar cells comprises the following components: spherical silver powder has a content of 45wt.%, flaky silver-coated copper powder has a content of 45wt.%; the flexible thermosetting compound is a mixed prepolymer of terminal hydroxyl polybutadiene and blocked isocyanate, and the content is 2.5wt.%; the epoxy resin is bisphenol A epoxy resin, and the content is 2.0wt.%; the compound curing agent is compound curing agent A, and the content is 1.2wt.%; the active diluent is ethylene glycol diglycidyl ether, and the content is 1.0wt.%, the inactive diluent is diethylene glycol ethyl ether acetate, and the content is 2.5wt.%; the auxiliary agent is sorbitan trioleate, and the content is 0.8wt.%.

[0051] A method for preparing a low-temperature curing conductive adhesive for a perovskite-silicon heterojunction tandem solar cell comprises the following steps:

[0052] Step 1: Mix the flexible thermosetting compound, epoxy resin, compound curing agent, diluent and additive according to the proportion, stir the materials in the container with a disperser to make them evenly mixed, and then add the conductive powder according to the proportion;

[0053] Step 2: Use a dispersing mixer to stir all the materials in the container to make them evenly mixed, and let them stand for 5 hours to allow the powder to be fully infiltrated to obtain a premixed mixture;

[0054] Step 3: Use a three-roll mill to further disperse and mix the mixture so that each component is evenly dispersed; wherein the gap between the discharge rollers of the three-roll mill is 10um;

[0055] Step 4: The rolled mixture is filtered through a 500-mesh filter to remove large-sized agglomerates and conductive powder to obtain a low-temperature curing conductive adhesive for perovskite-silicon heterojunction stacked solar cells.

[0056] The ambient temperature during the above preparation process is 20-25° C., and the ambient humidity is ≤65RH%.

[0057] Embodiment 2:

[0058] A low-temperature curing conductive adhesive for perovskite-silicon heterojunction stacked solar cells comprises the following components: spherical silver-coated nickel powder has a content of 46wt.%, flaky silver powder has a content of 46wt.%; the flexible thermosetting compound is a prepolymer of a compound containing an isocyanate group and a polyester polyol, with a content of 2.5wt.%; the epoxy resin is bisphenol F epoxy resin, with a content of 2.6wt.%; the compound curing agent is compound curing agent B, with a content of 0.8wt.%; the diluent is N-methylpyrrolidone, with a content of 1.6wt.%; and the auxiliary agent is castor oil polyoxyethylene ether, with a content of 0.5wt.%.

[0059] The preparation method of Example 2 is the same as that of Example 1.

[0060] Embodiment 3:

[0061] A low-temperature curing conductive adhesive for perovskite-silicon heterojunction stacked solar cells comprises the following components: 20wt.% of copper-tin-silver alloy powder, 46wt.% of flaky silver powder, and 25wt.% of spherical copper powder; the flexible thermosetting compound is a mixed prepolymer of epoxidized polybutadiene and blocked isocyanate, with a content of 3.0wt.%; the epoxy resin is a phenolic epoxy resin, with a content of 2.0wt.%; the compound curing agent is a compound curing agent C, with a content of 0.8wt.%; the diluent is ethylene glycol ethyl ether acetate, with a content of 2.7wt.%, and the auxiliary agent is ethylene glycol fatty acid ester, with a content of 0.5wt.%.

[0062] The preparation method of Example 3 is the same as that of Example 1.

[0063] Comparative Example 1:

[0064] A conductive adhesive, the components of which are different from those of Example 1, in that the curing agent is microcapsule type 2-ethyl-4-methylimidazole, the content of which is 0.8wt.%, and the inactive diluent is diethylene glycol ethyl ether acetate, the content of which is 2.9wt.%. The preparation method of Comparative Example 1 is the same as that of Example 1.

[0065] Comparative Example 2:

[0066] A conductive adhesive, the components of which are different from those of Example 2 in that: the curing agent is triethanolamine boron trifluoride, the content of which is 0.4wt.%, and the diluent is N-methylpyrrolidone, the content of which is 2.0wt.%. The preparation method of Comparative Example 2 is the same as that of Example 1.

[0067] Comparative Example 3:

[0068] A conductive adhesive, the components of which are different from those of Example 3 in that: the curing agent is triethanolamine, the content of which is 0.6 wt.%, and the diluent is ethylene glycol ethyl ether acetate, the content of which is 2.9 wt.%. The preparation method of Comparative Example 3 is the same as that of Example 1.

[0069] The conductive adhesives prepared in the above-mentioned Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to performance tests, including conductive adhesive viscosity test, printing test, film layer adhesion test and conversion efficiency test.

[0070] The viscosity of the conductive adhesive was tested using a Mars 40 rheometer with a cone-plate rotor at a test temperature of 25°C.

[0071] Printing test:

[0072] S1: Print the prepared conductive adhesive on a perovskite-silicon heterojunction stacked silicon substrate through a 28 μm opening non-grid screen to obtain a sample;

[0073] S2: Place the printed sample in an oven and cure it according to the following curing process parameters: drying at 120°C for 5 minutes and curing at 140°C for 10 minutes;

[0074] S3: Use an EL tester to test the printing quality of the sample.

[0075] The film adhesion test was conducted by tearing the screen-printed conductive adhesive with 3M 600# tape.

[0076] The performance test results are shown in Table 1:

[0077] Table 1 Performance test results

[0078]

[0079] Examples 1 to 3 use the preferred compound curing agent of the present invention. The low-temperature curing conductive adhesive prepared therefrom for perovskite-silicon heterojunction stacked solar cells has excellent viscosity stability, a long application period, and excellent fine line printing performance. After low-temperature (140°C) and short-time (10 min) curing, the printed film layer is completely cured, has the advantages of strong adhesion and excellent electrical properties, and achieves a higher photoelectric conversion efficiency. It is particularly suitable for preparing grid line electrodes for perovskite-silicon heterojunction stacked solar cells.

[0080] Compared with Example 1, the conductive adhesive of Comparative Example 1 uses a traditional microcapsule type imidazole curing agent. The prepared conductive adhesive will slowly cure itself when stored for a long time in a low temperature environment, greatly affecting its printability. The curing condition of this conductive adhesive is to cure at 150°C for 30 to 60 minutes. It cannot be completely cured under the curing conditions of low temperature and short time (140°C, 10 minutes). The finished screen-printed product will fall off when the 3M tape is torn off. At the same time, the conversion efficiency is low and the electrical performance is poor.

[0081] Compared with Example 2, Comparative Example 2 only uses triethanolamine boron trifluoride as a curing agent, and the curing temperature of the prepared conductive adhesive is greater than 180°C. It cannot be completely cured under low temperature and short time (140°C, 10 minutes) curing conditions. The screen-printed finished product will fall off when the 3M tape is torn off. At the same time, the conversion efficiency is low and the electrical performance is poor.

[0082] Compared with Example 3, Comparative Example 3 only uses triethanolamine as a curing agent, and the curing conditions of the prepared conductive adhesive are curing at 90°C for 4 hours or curing at 120°C for 2 hours. Compared with the conductive adhesive prepared in Example 3, the curing time of this conductive adhesive is longer, and it cannot be completely cured under the curing conditions of low temperature and short time (140°C, 10 minutes). The finished screen-printed product will fall off when the 3M tape is torn off, and the conversion efficiency is low and the electrical performance is poor. Moreover, this conductive adhesive will slowly cure when stored for a long time in a low temperature environment, which greatly affects its printability.

[0083] The present invention also provides other embodiments, and the specific preparation method is the same as that of embodiment 1.

[0084] Embodiment 4:

[0085] A low-temperature curing conductive adhesive for perovskite-silicon heterojunction stacked solar cells comprises the following components: spherical silver powder has a content of 42wt.%, flaky silver-coated copper powder has a content of 45wt.%; the flexible thermosetting compound is a mixed prepolymer of terminal hydroxyl polybutadiene and blocked isocyanate, and the content is 3.6wt.%; the epoxy resin is bisphenol A epoxy resin, and the content is 4.4wt.%; the compound curing agent is compound curing agent A, and the content is 2.2wt.%; the active diluent is ethylene glycol diglycidyl ether, and the content is 1.0wt.%, the inactive diluent is diethylene glycol ethyl ether acetate, and the content is 1.2wt.%; the auxiliary agent is sorbitan trioleate, and the content is 0.6wt.%.

[0086] Embodiment 5:

[0087] A low-temperature curing conductive adhesive for perovskite-silicon heterojunction stacked solar cells comprises the following components: spherical silver-coated nickel powder has a content of 44wt.%, flaky silver powder has a content of 45wt.%; a flexible thermosetting compound is a prepolymer of a compound containing an isocyanate group and a polyester polyol, with a content of 4wt.%; an epoxy resin is a bisphenol F epoxy resin, with a content of 3.1wt.%; a compound curing agent is a compound curing agent B, with a content of 1.1wt.%; a diluent is N-methylpyrrolidone, with a content of 1.9wt.%; and an auxiliary agent is castor oil polyoxyethylene ether, with a content of 0.9wt.%.

[0088] Embodiment 6:

[0089] A low-temperature curing conductive adhesive for perovskite-silicon heterojunction stacked solar cells comprises the following components: 20wt.% of copper-tin-silver alloy powder, 46wt.% of flaky silver powder, and 24wt.% of spherical copper powder; the flexible thermosetting compound is a mixed prepolymer of epoxidized polybutadiene and blocked isocyanate, with a content of 2.0wt.%; the epoxy resin is a phenolic epoxy resin, with a content of 1.8wt.%; the compound curing agent is a compound curing agent C, with a content of 0.6wt.%; the diluent is ethylene glycol ethyl ether acetate, with a content of 4.9wt.%, and the auxiliary agent is ethylene glycol fatty acid ester, with a content of 0.7wt.%.

[0090] The above-mentioned embodiments 4 to 6 provide a low-temperature curing conductive adhesive for perovskite-silicon heterojunction stacked solar cells, with a curing temperature of less than 150°C, a curing time of less than 15 minutes, excellent fine line printing performance, high photoelectric conversion efficiency, and a long application period.

[0091] The embodiments described above are merely descriptions of preferred implementations of the present invention and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope of the present invention.

Claims

1. A low-temperature curing conductive adhesive for perovskite-silicon heterojunction tandem solar cells, characterized in that: Calculated by mass percentage, it includes: 85~95wt.% conductive powder, 1~10wt.% flexible thermosetting compound, 1~10wt.% epoxy resin, 0.1~10wt.% compound curing agent, 1~5wt.% diluent, and 0.1~1wt.% auxiliary agent; The composite curing agent comprises component A and component B; The component A is one of the following formulas: (i) By mass, the ratio of boron trifluoride complex, borofluoride metal salt, organic sulfonic acid and tertiary amine compound is (3-8): (3-5): (1-3): 1; (ii) The ratio of boron trifluoride complex, acetylacetonate metal salt and tertiary amine compound is (3-8): (1-2): 1, calculated by mass. The component B includes one or two of benzyl alcohol and polyethylene glycol.

2. The low-temperature curing conductive adhesive for perovskite-silicon heterojunction tandem solar cells according to claim 1, characterized in that: Component B of the composite curing agent includes benzyl alcohol and polyethylene glycol. In parts by mass, the ratio of component A, benzyl alcohol and polyethylene glycol of the composite curing agent is (1.5-5): (1-2.5):

1.

3. The low-temperature curing conductive adhesive for perovskite-silicon heterojunction tandem solar cells according to claim 1, characterized in that: In the composite curing agent, the boron trifluoride complex is selected from one or more of boron trifluoride ethyl ether, boron trifluoride phenol, boron trifluoride piperidine, boron trifluoride acetate, boron trifluoride monomethylamine, boron trifluoride monoethylamine, boron trifluoride triethanolamine, boron trifluoride monoethanolamine, boron trifluoride-2,4-dimethylaniline, and boron trifluoride benzylamine.

4. The low-temperature curing conductive adhesive for perovskite-silicon heterojunction tandem solar cells according to claim 1, characterized in that: The tertiary amine compound is selected from one or more of N,N-dimethyl-2-hydroxy-decylamine, triethanolamine, N,N-diethyl-2-hydroxy-hexadecylamine, and 2,4,6-tris(dimethylaminomethyl)phenol.

5. The low-temperature curing conductive adhesive for perovskite-silicon heterojunction tandem solar cells according to claim 1, characterized in that: In the composite curing agent, the acetylacetonate metal salt is selected from one or more of acetylacetonate aluminum salt, acetylacetonate zinc salt, acetylacetonate indium salt, acetylacetonate copper salt, and acetylacetonate nickel salt; and the organic sulfonic acid is selected from one or more of benzenesulfonic acid, cycloalkanesulfonic acid, and p-toluenesulfonic acid.

6. The low-temperature curing conductive adhesive for perovskite-silicon heterojunction tandem solar cells according to claim 1, characterized in that: The conductive powder is one or more of silver powder, silver-coated copper powder, silver-coated nickel powder, copper powder, and copper-tin-silver alloy powder; the conductive powder has a spherical powder and a flaky powder, and the mass ratio of the spherical powder to the flaky powder is (99:1) to (1:99); The particle size distribution of spherical powder is D90≤6μm, D50≤4μm, tap density is 3~8g / ml, and specific surface area is 0.2~2.5m 2 / g; The flake powder has a flake size distribution of D90≤15μm, D50≤8μm, a tap density of 3-8g / ml, and a specific surface area of ​​0.3-1.5m 2 / g.

7. Use of a low-temperature curing conductive adhesive for perovskite-silicon heterojunction tandem solar cells according to any one of claims 1 to 6 in preparing grid line electrodes for perovskite-silicon heterojunction tandem solar cells.

8. A grid line electrode of a perovskite-silicon heterojunction tandem solar cell, characterized in that: The grid line electrode of the perovskite-silicon heterojunction tandem solar cell is prepared by using the low-temperature curing conductive adhesive for perovskite-silicon heterojunction tandem solar cells described in any one of claims 1 to 6 through a screen printing process and / or a mesh-free screen.

Citation Information

Patent Citations

  • Conductive silver adhesive composition with low contact resistivity with TCO transparent conductive film layer

    CN114121339A

  • Method for making epoxy resin polymer having low electronic impedance its products and application

    CN1275593A